BUILDING THE CAPACITY OF ORGANIC FARMERS IN PRIJEKNGABLAK VILLAGE FOR INDEPENDENT PRODUCTION OF BIOPESTICIDES AND LIQUID ORGANIC FERTILIZERS - Mahbubillah, M. Ainul; Redjeki, Endah Sri; Khakim, Arsanul; Ayuni, Rieke Dwi; Rohmah, Laila Ainur (Fakultas Pertanian, 2024)
In 2012, Prijekngablak Village, Karanggeneng, Lamongan, faced crop failure due to an uncontrollable pest outbreak. This prompted the Rame Gawe II Farmers' Group to initiate organic farming, despite various social challenges. In 2022, the village government supported these efforts, enabling the community to produce liquid organic fertilizer (POC) and bio-pesticides. However, obstacles such as low public trust, poor institutional coordination, and inadequate laboratory facilities persisted. The Community Service team addressed these issues through focus group discussions (FGDs), facility improvements, laboratory management enhancements, and training on producing and applying POC and bio-pesticides. FGDs revealed that 54.3% of farmers had a strong understanding of organic farming, 62.9% moderately understood its benefits, 51.4% had practical experience, and 77.1% were willing to adopt it. Laboratory improvements and SOP implementation improved production performance. Key products included POC from water hyacinths, bio-pesticides containing Beauveria bassiana and Trichoderma sp., and PGPR isolated from local bamboo roots. Their application enhanced plant health and reduced pest and disease attacks, showcasing the potential of organic farming in overcoming agricultural challenges in the village.